PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KEGUNAAN TERHADAP KEPUASAN PENGGUNA: SURVEI PADA PENGGUNA SISTEM INFORMASI “MOKA POINT OF SALE” - Leihitu, Rizky Ruth; Pattiwaellapia, Ongen Stembri; Sulistiyarini, Sulistiyarini; Fatchuroji, Acep; Nurficahyanti, Fera (Jurnal Ilmu Administrasi dan Bisnis, 2020)
This study aims to analyze the influence of system quality, information quality, and usability on "Moka Point of Sale" user satisfaction. Data was collected in June 2018. The population in this study were all cashiers, managers, and owners who use the Moka POS information system in the field of coffee shop business in Yogyakarta. Sampling using a purposive sampling method. Data analysis methods include descriptive analysis and quantitative analysis with structural equality model (SEM) analysis technKIues. The result of this study are system quality has a positive influence on user satisfaction, which the effect of system quality on user satisfaction will be greater if mediated by usefulness. Information quality has a positive effect on user satisfaction, which the effect of information quality on user satisfaction will be greater if mediated by usefulness.